Analysis of Linear Regression Level of Customer Satisfaction New Smartphone Purchase Decisions - Priatno; Bilal Abdul Wahid (Institute of Computer Science (IOCS), 2021)
Smartphone technology is currently implementing the latest and most comprehensive technology, which in addition to this technology also allows you to do many things such as making video conferences, playing e-sport games, and other transactions. Research conducted by the author uses the SPSS Ver.22 application program to report the data obtained by distributing questionnaires to 80 respondents who will buy or have used new smartphone products. After the analysis is carried out, the results obtained from the independent variables are based on brand (X1), price (X2), product specifications (X3), design (X4), and together have a positive effect on the related variables, namely the purchase decision (Y), so that the following equation is obtained: Y = 7.244 - 0.012X1 + 0.210X2 + 0.464X3 - 0.003X4.